Meningkatkan Kemandirian Dalam Merawat Diri Pada Pasien Dengan Fraktur Femur 1/3 Proksimal Dektra Post ORIF Hari Ke-2 Di RSOP. DR. R. Soeharso Surakarta - Lesmana, Ade Cahya, Enita Dewi , S.Kep.,Ns.,M.N, Arina Maliya, S.Kep., Ns.,M.Si., Med (2016)
ORIF surgery patients after experiencing limitations in performing daily activities -day associated with reduced muscle tone. That the lack of motion causes decreased muscle strength, so that the patient's loss of independence in caring for him. Self-care is a daily activity - the day in taking care of himself, either used no tools or using tools. The purpose of this scientific publication manuscript is to describe nursing care in patients with reduced mobility in enhancing self-reliance in caring for him, including assessment, intervention, implementation, evaluation. The method used in the writing of this scientific publication yaiu using descriptive method with case study approach that explain and perform the nursing process. The nursing process of assessment to the evaluation done nursing. Nursing action 3 x 24 hours at pasiaen post opearasi in improving independence in self-care, nursing actions do is help you access to the bathroom, with toiletries and give an explanation of how the shower on the bed with or without the use of soap, motivate patients about the ability of the patient, to train the patient's own bathroom with the family as a provision for independent monitoring after returning home to minimize dependence on others, trains run using tools such as crack, act ROM (Range of Motion). The exercise program can strengthen muscles and increase the independence, Patient able to indulge aided by tools, patient confidence back, independence in caring for her patients increased.The results can be used as a basis for nursing interventions in the form of activities such as exercise, eating, personal care, bathing, toileting use by integrating the management of pain in post rehabilitation phase ORIF lower limbfractures. Keywords: Post ORIF, self-reliance, self Caring, Nursing, Fracture.